A Demand Systems Analysis of Energy Sources in the United States - Bakhtavoryan, Rafael (International Journal of Energy Economics and Policy, 2025)
This study estimates a Generalized Exact Affine Stone Index model to quantify demand structure among such energy sources as natural gas, coal, nuclear, wind, solar, and geothermal energy, employing monthly time-series data ranging from January of 2009 through December of 2020. The demand for natural gas, coal, and nuclear energy emerges as inelastic. A significant substitutability relationship is empirically established between the energy sources. All the computed expenditure elasticities are positive, with natural gas being the most sensitive and nuclear energy being the least sensitive to energy source expenditures. Pre-committed consumption is found for geothermal energy. Finally, the welfare implications of the projected decrease in the natural gas price are assessed with the Hicksian compensating variation measure.